2019
DOI: 10.3390/rs11243046
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lake Area in Response to Climatic Forcing in the Endorheic Hongjian Lake Basin, China

Abstract: Endorheic lakes are key components of the water cycle and the ecological system in endorheic basins. The endorheic Hongjian Lake wetland is China’s national nature reserve for protecting the vulnerable species of Relict Gull. The Hongjian Lake, once China’s largest desert freshwater lake, has been suffering from severe shrinkage in the last two decades, yet the variations in the lake area and its responses to climate change are poorly understood due to a lack of in situ observations. In this study, using Lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…This study provides a valuable supplement to these previous studies and can address the gaps in simulating detailed hydrologic processes related to lakes. In the HJN watershed, previous studies identified precipitation and evaporation (or temperature) as the meteorological driving factors influencing lake variations [68][69][70], and surface runoff and evaporation were identified as the hydrologic driving factors [30]. These results were consistent with the annual mass balance in our study.…”
Section: Comparison With Previous Studiessupporting
confidence: 91%
See 1 more Smart Citation
“…This study provides a valuable supplement to these previous studies and can address the gaps in simulating detailed hydrologic processes related to lakes. In the HJN watershed, previous studies identified precipitation and evaporation (or temperature) as the meteorological driving factors influencing lake variations [68][69][70], and surface runoff and evaporation were identified as the hydrologic driving factors [30]. These results were consistent with the annual mass balance in our study.…”
Section: Comparison With Previous Studiessupporting
confidence: 91%
“…Liang and Li (2019) [69] reported that precipitation and ET had a positive and negative correlation, respectively, with the area of HJN Lake. The coefficient of correlation varied at monthly, seasonal, and annual time scales.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Liang et al (2017), Li (2020), and Wang(2018b) found that severe human activity, as well as climate warming, lead to a fast decrease in the area of Hongjiannao Lake in 1999-2015. When considering time lag, the correlation coefficient between climatic factors and human activities significantly increased (Liang and Li, 2019). Yue and Liu (2019a) used a ridge regression method to establish a regression model between lake area, water level, lake volume variations, and influencing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have been put forward to analyze the changes of the lake area, water level, and lake volume and the dynamics to climate change and human activities by using remote sensing techniques and hydrological models (Ma et al, 2014;Liang, 2019;Liang and Yan, 2017;Yan et al, 2018;Wang et al, 2018a;Zhao et al, 2018;Liang and Li, 2019;Yue and Liu, 2019). Indeed, Hongjiannao Lake has been largely neglected in hydrological research, as it receives less attention and lacks management compared with large lakes and reservoirs which have traditionally been managed and monitored.…”
Section: Introductionmentioning
confidence: 99%
“…5). Two physical features prevail: lake water extent (Buma et al 2018; Liang and Li 2019; Nitze et al 2020; Bai et al 2021; Chowdhury et al 2021; Zhang et al 2021), and ice cover (Sun et al 2018; Wang et al 2018; Carrea et al 2023). However, during the last years few studies use EO also to address ecological shifts.…”
Section: Resultsmentioning
confidence: 99%